2023
DOI: 10.1111/all.15825
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gut epithelial barrier impairment caused by food emulsifiers polysorbate 20 and polysorbate 80

Ismail Ogulur,
Duygu Yazici,
Yagiz Pat
et al.

Abstract: BackgroundThe rising prevalence of many chronic diseases related to gut barrier dysfunction coincides with the increased global usage of dietary emulsifiers in recent decades. We therefore investigated the effect of the frequently used food emulsifiers on cytotoxicity, barrier function, transcriptome alterations, and protein expression in gastrointestinal epithelial cells.MethodsHuman intestinal organoids originating from induced pluripotent stem cells, colon organoid organ‐on‐a‐chip, and liquid–liquid interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 60 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…The two frequently used food emulsifiers, polysorbates 20 and 80, were recently reported for their cellular toxicity, damage to epithelial barriers, transcriptome alterations, and protein expression in gastrointestinal epithelial cells. Although 1% is allowed, epithelial barrier disruption, upregulation of apoptosis, inflammatory responses, and stress responses were observed at 20 times lower (0.05%) concentrations ( 71 ). Moreover, the consumption of processed foods has been linked to various health issues, including all-cause mortality, obesity, metabolic syndrome, and depression ( 72 ).…”
Section: Changes In the Exposome And Exposure To Environmental Toxic ...mentioning
confidence: 99%
“…The two frequently used food emulsifiers, polysorbates 20 and 80, were recently reported for their cellular toxicity, damage to epithelial barriers, transcriptome alterations, and protein expression in gastrointestinal epithelial cells. Although 1% is allowed, epithelial barrier disruption, upregulation of apoptosis, inflammatory responses, and stress responses were observed at 20 times lower (0.05%) concentrations ( 71 ). Moreover, the consumption of processed foods has been linked to various health issues, including all-cause mortality, obesity, metabolic syndrome, and depression ( 72 ).…”
Section: Changes In the Exposome And Exposure To Environmental Toxic ...mentioning
confidence: 99%
“…Ultra‐processed foods contain high levels of dietary advanced glycation end products, which may facilitate food allergy by impairing the gut barrier and by inducing immune dysfunction 107 . Furthermore, food emulsifiers induce a pro‐inflammatory response in intestinal epithelial barriers and cause direct cell toxicity at high concentrations 108 . Food colourants have been shown to cause epithelial damage in mice via myosin light chain kinase activation 109 …”
Section: Causes Of Epithelial Barrier Dysfunctionmentioning
confidence: 99%
“…Studies suggest that these products may enhance bacterial translocation across mucosal surfaces, affect the gut epithelial mucous layer, alter microbial composition, and contribute to the development of intestinal inflammation. 126 127 128 129 Recent study has shown that commonly used food emulsifiers, polysorbate 20 and polysorbate 80, cause cell death at daily-used concentrations, directly impair barrier integrity of gut epithelial cells, and cause molecular toxicity and proinflammation at lower doses. 129 …”
Section: External Exposome In Epithelial Barrier Damagementioning
confidence: 99%
“… 126 127 128 129 Recent study has shown that commonly used food emulsifiers, polysorbate 20 and polysorbate 80, cause cell death at daily-used concentrations, directly impair barrier integrity of gut epithelial cells, and cause molecular toxicity and proinflammation at lower doses. 129 …”
Section: External Exposome In Epithelial Barrier Damagementioning
confidence: 99%